Quo vadis [videorecording (DVD)] - LeRoy, Mervyn, 1900-1987; Behrman, S. N. (Samuel Nathaniel), 1893-1973; Levien, Sonya, 1888?-1960; Surtees, Robert; Skall, W. V. (William V.), 1898-1976; Rózsa, Miklós, 1907-1995; McCoy, Herschel, 1912-1956; Taylor, Robert, 1911-1969; Kerr, Deborah, 1921-2007; Ustinov, Peter; Genn, Leo, 1905-1978; Laffan, Patricia, 1919-2014; et al. (Distributed by Warner Home Video, 2008)
Returning to Rome after 3 years in the field, General Marcus Vinicius meets and falls in love with the devout Christian, Lygia. She doesn't want to have anything to do with the warrior. Though Lygia grew up Roman, and as the adopted daughter of a retired general, Lygia is technically a hostage of Rome. Marcus gets Emperor Nero to give her to him for services rendered. Lygia is not happy about this situation, but she falls in love with Marcus anyway. Meanwhile, Nero's atrocities get more outrageous. When he burns Rome and blames the Christians, Marcus goes off to save Lygia and her family. Nero captures them and all other Christians. He decides to make a sport of it by throwing them to the lions.